Magnetochronology and age models of deposition of the Melka Kunture stratigraphic sequence (Upper Awash, Ethiopia) and age assessments of the main archeological levels therein contained. (15th December 2021) - Perini, Serena; Muttoni, Giovanni; Monesi, Edoardo; Melis, Rita T.; Mussi, Margherita
Abstract: We present new magnetostratigraphic results from the Melka Kunture sedimentary sequence outcropping along the Gombore and Garba gullies in the Upper Awash Valley of Ethiopia that provide a new temporal framework for human presence in this area of the Ethiopian plateau in the Pleistocene. We obtained a time-diagnostic sequence of normal and reverse polarity magnetozones representing a relatively continuous magnetochronologic record extending from the Brunhes Chron at the top to the Olduvai Subchron or possibly the Reunion Subchron at the base, assembled from 9 stratigraphic sections correlated in a regional lithostratigraphic context. By integrating our chronology provided by paleomagnetism with 40 Ar/ 39 Ar dating from the literature, we generated simple yet reliable and testable age models of deposition for the Melka Kunture sedimentary sequence that we used to estimate the mean ages of the main archeological levels therein contained that resulted ranging from ∼0.6 Ma to ∼2.1 Ma thus representing altogether one of the most persistent and prolonged records of human presence of the entire African continent. Highlights: Magnetostratigraphy reveals that the Melka Kunture stratigraphy extends in substantial continuity from the Brunhes Chron to the Olduvai Subchron. Age models of deposition based on magnetochronology and geochronology reveal that the sequence deposited from ∼0.6 to ∼2.1 Ma. All main archeological levels in the Melka Kunture stratigraphy have been assigned numerical age estimates with errors. Melka Kunture represents one of the most extended - and now dated - records of human presence in Africa in the Pleistocene.